1994
DOI: 10.1177/0022022194252003
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Ethnic Status, and Ideological Asymmetry

Abstract: In two studies, the authors examined the relationship between desire for group-based dominance (i.e., SDO), gender, and group attachment. As expected, the relationship between social dominance orientation and gender was invariant across ethnic groups. Across ethnic groups, males were found to have higher levels of social dominance orientation than were females. Furthermore, for members of high-status groups, there were positive relationships between desire for group-based dominance and group affiliation, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 37 publications
6
82
1
3
Order By: Relevance
“…Specifically, they found that SDO was highly correlated with, among many variables, opposition to both social programs and racial policies. Sidanius et al (1994) found that among Americans of lower group status (i.e., African Americans and Latino Americans), a relationship exists between SDO and high-status group favoritism. For these individuals, SDO was negatively correlated with ingroup salience and relative closeness to one's ingroup.…”
Section: Social Dominance Orientationmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, they found that SDO was highly correlated with, among many variables, opposition to both social programs and racial policies. Sidanius et al (1994) found that among Americans of lower group status (i.e., African Americans and Latino Americans), a relationship exists between SDO and high-status group favoritism. For these individuals, SDO was negatively correlated with ingroup salience and relative closeness to one's ingroup.…”
Section: Social Dominance Orientationmentioning
confidence: 99%
“…It is conceivable that some members of low-status groups (say, African Americans in a social system like the United States) who score high on SDO scales will support the hierarchy within which they currently live-even a system that subordinates their ingroup. These high-SDO individuals manage with the constraints imposed by low-status group membership by disaffiliating with the ingroup and favoring the high-status group or groups, thus resulting in the expression of outgroup favoritism (Jost, 1995;Jost & Banaji, 1994;Mullen et al, 1992;Sachdev & Bourhis, 1987;Sidanius, 1993;Sidanius et al, 1994;Tajfel & Turner, 1986).…”
Section: Sdo and Group Positionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sidanius, Pratto, and Rabinowitz (1994) defined legitimizing myths as group-relevant "sociopolitical attitudes, ideologies, opinions, beliefs, values, causal attributions, and public policy initiatives that either express support for, or opposition to, the redistribution of social value among social groups (e.g., social classes, ethnic/racial groups, genders, nations). .…”
Section: Consequences Of Language Lossmentioning
confidence: 99%